Motivations and spatial behavior of OHV recreationists: A case-study from central Utah (USA). (December 2021) - Smith, Jordan W.; Miller, Anna B.; Lamborn, Chase C.; Spernbauer, Bettina S.; Creany, Noah; Richards, Jacob C.; Meyer, Caleb; Nesbitt, Jordan; Rempel, Will; Wilkins, Emily J.; Miller, Zachary D.; Freimund, Wayne; et al.
Abstract: Despite the growing popularity of off-highway vehicle (OHV) recreation, only a small body of research has focused on the motivations of these recreationists, how motivations vary across participants, and how motivations are related to recreationists' on-site behavior. Our investigation integrates established theory from the field of outdoor recreation management to develop a better understanding of the diverse motivations of OHV users visiting the Sheeprock Mountains region of central Utah, USA. We pair data on OHV users' recreation experience preferences with data on their spatial behavior to develop strategic approaches for resource management. This can help balance the trade-offs between maintaining the quality and diversity of outdoor recreation experiences while limiting resource impacts. Our analyses revealed the motivations of OHV users were not related to a variety of variables characterizing OHV users' rides (e.g., distance, speed, etc.). However, we did find distinct differences in the routes favored by OHV users preferring different outdoor recreation experiences. We visualize the concentration of routes preferred by OHV users with different experience preferences to inform the development of spatially targeted interpretation and signage efforts. Through this approach, we demonstrate how a better understanding of the diverse motivations of OHV users can be used to inform communication strategies designed to get the most meaningful information in front of the right users in the right places. Management implications: The motivations of OHV users were not related to a variety of variables characterizing the OHV users' rides. There were distinct differences in the routes favored by OHV users preferring different outdoor recreation experiences. We document a method for visualizing the concentration of routes preferred by OHV users with different experience preferences. Visualizations of the concentration of routes preferred by OHV users with different experience preferences can be used to inform the development of spatially targeted interpretation and signage efforts.